Annotated Checklist of California Encyrtidae (Hymenoptera) - Zuparko, Robert L. (Zootaxa, 2015)
Based on examination of the literature and specimens, 208 described species in 90 genera of Encyrtidae are listed from California. Data on the original publication, deposition of types, geographic distribution and host records of these species are presented. Forty-three species were established in biocontrol programs, 157 are presumed native, 7 appear to be adventitious introductions, and the origin of one is undetermined. An additional 276 morphospecies are also listed as present in the state within an additional 21 described genera and potentially up to 20 undescribed genera. Altogether, 31 new genera and 36 new species are recorded for the state, as well as 70 new parasitoid-host records.        Errors pertaining to California taxa in previously published papers are corrected. Metaphycus immaculatus (Howard) is reported as a new combination (from Aphycus Mayr).        Three appendices are included: a host/parasitoid listing for the described species present in the state, a listing of taxa previously reported from California under invalid names, and a list of taxa either erroneously reported from the state, or unsuccessful biocontrol introductions.